Financial Management and Assets Ownership Toward Subjective Well-Being on Entrepreneurial Family - Hani Setyasalma; Istiqlaliyah Muflikhati (Journal of Consumer Sciences, 2019)
This study aims to analyze the effect of financial management and asset ownership on subjective well-being on entrepreneurial families. This research was conducted on 90 families who had a business in Babakan Village, Dramaga District, Bogor Regency. The sampling method was using the purposive technique. Respondents in this study are husband or wife who owns and manage their business. Data analyzed descriptively and inferential statistics using multiple linear regression test. According to the research, entrepreneurial families have a low financial management index. Most families have assets at least three types. The level of subjective well-being of the entrepreneurial family is classified as moderate. Income and financial management have a significant positive effect on the subjective well-being of families. Asset ownership does not have a significant effect on subjective family well-being.